Financing for development and middle income-countries : new challenges (UN ECLAC SantiagoCL, 2011)
Argues that international cooperation should search for a comprehensive and broad-based response to the development problem, one that not only addresses the needs of low-income countries but also considers the diverse needs and kinds of vulnerabilty present in middle-income countries (MIC).
Keywords: DEVELOPMENT AID